Learning strategies and the understanding of written texts in the English language - Prado-Huarcaya, Diana L. (2020)
This study responds to the attempt to establish the degree of relationship that exists between learning strategies with the understanding of written texts of the English language in the students of the Language Center of a Private University of Lima-North-2019. This research is non-experimental, descriptive and correlational design. It was carried out with a sample of 20 students from the Language Center. For data collection, a test questionnaire was applied per variable, which was previously validated according to the objectives of the study. The results indicate the existence of a significant correlation between learning strategies and reading comprehension, the significance value obtained being r=7,96, (p-valor <0.05). Concluding that there is a significant relationship between the variables learning strategies and comprehension of written texts of the English language.